Effects of Dietary Supplementation of Propolis on Performance, Egg Quality and Blood Parameters of Layer Quails - ŞENTÜRK, E.T.; YILDIZ, A.Ö.; OLGUN, O.; MUTLU, M. (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of this study was to investigate the effect of addition of different levels of propolis to the layer quail diets on performance, egg quality and blood parameters. In the experiment, a total of 120 quails at the age of 22 weeks were randomly distributed to six treatments groups, each with four subgroups. There were 5 quails in each subgroup and the trial lasted 12 weeks. Treatments diets were prepared by adding 0, 2, 4, 6, 8 or 10 g/kg propolis to the basal diet. Body weight change, egg production, egg weight and feed intake were not affected by the addition of propolis to the diet (P>0.05). The egg mass (P<0.01) and feed conversion ratio (P<0.05) linearly improved by addition of propolis. The eggshell breaking strength (P<0.05),eggshell thickness (P<0.01) and Haugh unit (P<0.01) improved by the addition of propolis but other egg quality parameters were not affected (P>0.05).The haematological parameters of the blood were not affected of propolis to the diet (P>0.05), except for the neutrophil content, which was quadratically affected by the addition of propolis, and increased at doses up to 6 g/kg but decreased at the levels of 8 or 10 g/kg (P<0.05). The addition of propolis to the diet did not affect the serum parameters (P<0.05), except cholesterol (P<0.01) and calcium (P<0.05) contents in layer quails. The cholesterol content of serum was linearly affected by the addition of propolis and minimized at the dose of 8 g/kg. The calcium level increased when propolis was supplemented at the dose of 2 g/kg but linearly decreased with higher dose levels. According to these results, it can be said that the addition of 8 g/kg propolis to laying quail diets positively affected the egg mass, eggshell breaking strength, eggshell thickness and cholesterol concentration of serum, however, calcium metabolism was negatively affected by propolis levels.